Влияние алиментарной полифенольной недостаточности на цитоморфологические изменения в слизистой оболочке полости рта крыс = Influence of alimentary deficiency of polyphenol on the cytomorphological changes in the oral cavity mucosa of rats - Anna Nikolaeva (Kazimierz Wielki University, 2015)
Nikolaeva A. V. Влияние алиментарной полифенольной недостаточности на цитоморфологические изменения в слизистой оболочке полости рта крыс = Influence of alimentary deficiency of polyphenol on the cytomorphological changes in the oral cavity mucosa of rats. Journal of Education, Health and Sport. 2015;5(10):221-226. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32798 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A221-226 https://pbn.nauka.gov.pl/works/662967 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015.   УДК: 616.311:579.23 - 036.632: 599.323.4 UDC: 616.311:579.23 - 036.632: 599.323.4   ВЛИЯНИЕ АЛИМЕНТАРНОЙ ПОЛИФЕНОЛЬНОЙ НЕДОСТАТОЧНОСТИ НА ЦИТОМОРФОЛОГИЧЕСКИЕ ИЗМЕНЕНИЯ В СЛИЗИСТОЙ ОБОЛОЧКЕ ПОЛОСТИ РТА КРЫС   INFLUENCE OF ALIMENTARY DEFICIENCY OF POLYPHENOL ON THE CYTOMORPHOLOGICAL CHANGES IN THE ORAL CAVITY MUCOSA OF RATS   А. В. Николаева A. V. Nikolaeva   Государственное учреждение  «Институт стоматологии Национальной Академии Медицинских Наук Украины» SE «The Institute of Stomatology National Academy of Medical Sciences of Ukraine»   Реферат В работе изучено влияние хронической недостаточности растительных полифенолов в рационе питания крыс на морфологические изменения  в эпителии  слизистой оболочки полости рта. Опыты проведены на 14 белых крысах-самках, которые были помещены в 2 группы по 7 особей в каждой. Крысы 1-й группы (интактные) содержались на стандартном рационе вивария,  2-я группа крыс содержалась на рационе, лишенном алиментарных растительных полифенолов. Длительность эксперимента составила 70 дней. Таким образом, впервые было изучено влияние длительной недостаточности растительных полифенолов в рационе животных на морфологические изменения в эпителии слизистой оболочки полости рта. Хроническое лишение крыс растительной пищи вызвало существенные нарушения в эпителиальном пласте слизистой оболочки щеки.   Ключевые слова: морфологические исследования, эпителиоциты, алиментарная недостаточность растительных полифенолов, слизистая оболочка щеки, белые крысы.   • V. Nikolaeva   SE «The Institute of Stomatology National Academy of Medical Sciences of Ukraine» INFLUENCE OF ALIMENTARY DEFICIENCY OF POLYPHENOL ON THE CYTOMORPHOLOGICAL CHANGES IN THE ORAL CAVITY MUCOSA OF RATS   Summary   The Aim of this research was to study the influence of chronic insufficiency of the plant polyphenols in the diet of of rats on the morphological changes in the epithelium of of the oral mucosa. Materials and methods. The experiment was conducted on 14 white female rats, which were in 2 groups by 7 animals. The rats of first group (intact) were kept on a standard diet of the vivarium, the second - were kept on a diet devoid of alimentary plant polyphenols. The experiment lasted 70 days. Results and conclusions. For the first time studied the value of alimentary plant polyphenols to morphofunctional state of the oral mucosa. It is found, that chronic deprivation the rats of the plant food caused significant disorders in epithelial layer - the violation of cell division, cell differentiation, the state of the microvasculature of the buccal mucosa.   Key words: morphological studies, epitheliocytes, chronic insufficiency of the plant polyphenols, buccal mucosa, white rats.